Synthesis, Characterization, and Antibacterial Evaluation of New 2,3-Dihydroquinazoline-4-One Derivatives and their Laser Efficiency - Yassin, Nour Adnan; Juma, Fawzi Hamid (American Journal of Bioscience and Clinical Integrity, 2025)
In this study, a series of novel 2,3-dihydroquinazolin-4-one derivatives [N11–N15] were synthesized through a cyclization reaction between Schiff base intermediates and 2-aminobenzoic acid under mild conditions using tetrahydrofuran as the solvent and triethylamine as the catalyst. The synthesized compounds were structurally confirmed by UV-Vis, FT-IR, and NMR spectroscopic analyses, revealing key functional groups and characteristic transitions associated with quinazoline derivatives. Their antibacterial activity was evaluated against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative) using the well diffusion method. The compounds showed variable antimicrobial efficacy, with compound N11 demonstrating the highest inhibition zone, particularly against Staphylococcus aureus (3.2 cm at 0.1 mg/ml), outperforming the standard antibiotic ciprofloxacin in some concentrations. Furthermore, the effect of Nd:YAG laser irradiation on the structural integrity of the compounds was assessed, showing complete decomposition and color change to black charcoal, indicating significant photothermal instability. These results suggest the potential of hydroquinazoline derivatives as promising antibacterial agents, particularly against resistant Gram-positive pathogens.